The Effect of Sambang Darah Leaf Filtrate (Excoecaria Cochinchinensis L) to Reduce The Bleeding Time in Skin Wounds of White Rats (Rattus Norvegicus) - Baiq Isti Hijriani; Siti Zaetun; Ida Bagus Rai Wiadnya (Jurnal Analis Medika Biosains (JAMBS), 2023)
Hemostasis is the process of stopping bleeding from a damaged blood vessel. When bleeding occurs, the body will naturally respond with a hemostatic mechanism to stop the bleeding. Indonesian people have long used plants in medicine, one of which is sambang darah (Excoecaria cochinchinensis L) plant. Sambang darah has a chemical compound that is thought to stop bleeding. The purpose of this study was to determine the potential of sambang darah filtrate to reduce the bleeding time in skin wounds of white rats (Rattus norvegicus). This study is a pre-experimental study with a static group comparison approach. The number of experimental units in this study were 10 white rats which were divided into treatment group and control group. Data analysis used the Independent Sample T Test. The results showed that the average of bleeding time in the skin wounds of white rats without drops of sambang darah leaf filtrate was 252 seconds. While the average of bleeding time in the skin wounds of white rats with drops of sambang darah leaf filtrate is 163 seconds. The conclusion of this study is sambang darah (Excoecaria cochinchinensis L) leaf filtrate have a potential to reduce the bleeding time in the skin wounds of white rats (Rattus norvegicus).